Textbooks of Islamic education for secondary school in Malaysia and Somalia in the topic of akhlak: a comparative study - Ismail, Halim; Rusli, Siti Munirah; Shuib, Nur Shuhada; Yusuf, Amiin Jirde; Ismail, Noorazizi; Che Noh, Mohd Aderi (Turkish Journal of Physiotherapy and Rehabilitation, 2021)
Textbook is considered as an instructional material to help teachers to deliver the content of syllabus and to assist students to process information given by teachers. Based on the importance of the textbook, this study was intended to analyze and compare Malaysia’s form 2 Islamic Education textbook and Somalia ’s senior 1 Islamic Education textbook in Akhlaq’s field Methodology that have been used is document analysis. These data are analyzed based on the 5 main components of the textbook namely background of textbook, learning content, activities, assessments and graphics and illustrations. This study found that there are some strengths and weaknesses of Malaysia and Somalia textbooks from the aspects of learning content, activities, assessments and graphics and illustrations. This study has an impact towards both country’s textbook developers in improving the quality of it.